World Bank Group intends to enhance climate impact evaluation of their projects with FLW/GHGe impact assessment of value chain operations; the ACE calculator will be assessed for this function - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
Based on presentation of ACE calculator WB concluded that the way how ACE calculator assesses FLW and GHGe very well represents how WB wants to address it in their projects.